The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000363102
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aggression, Improved Spatial Memory, and Reduced Anxiety-Like Behaviour in Adult Male Mice Exposed to Fluoxetine Early in Life

Abstract: Rationale: Fluoxetine (Flx; brand names Prozac, Sarafem, Rapiflux), a selective serotonin reuptake inhibitor, is prescribed for the treatment of depression in pregnant women; however, this commonly prescribed medication could affect fetal brain development as Flx crosses the placenta. The available data concerning the anatomical and behavioural consequences of perinatal exposure to Flx during early development on adult behaviour are limited and often contradictory. Objectives: To further delineate the long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 90 publications
4
36
0
Order By: Relevance
“…Lisboa et al () reported that exposure to FLX during pregnancy and lactation had no effect on the number and duration of aggressive attacks in mice. In contrast, Kiryanova and Dyck () reported that exposure of mouse dams to high dose of FLX beginning on gestation Day 15 until postnatal Day 12 increased aggression of male mouse offspring. Along the same lines, it was shown that exposure to fluoxetine on gestation days 13–21 increased foot shock‐induced aggression in male offspring (Singh, Jaiswal, Singh, & Bhattacharya, ).…”
Section: Discussionmentioning
confidence: 93%
“…Lisboa et al () reported that exposure to FLX during pregnancy and lactation had no effect on the number and duration of aggressive attacks in mice. In contrast, Kiryanova and Dyck () reported that exposure of mouse dams to high dose of FLX beginning on gestation Day 15 until postnatal Day 12 increased aggression of male mouse offspring. Along the same lines, it was shown that exposure to fluoxetine on gestation days 13–21 increased foot shock‐induced aggression in male offspring (Singh, Jaiswal, Singh, & Bhattacharya, ).…”
Section: Discussionmentioning
confidence: 93%
“…These lower doses of fluoxetine may not be sufficient to alter offspring development, or there may be differences in offspring outcome if dams are treated with fluoxetine throughout gestation as well as postpartum. Furthermore, higher doses of maternal fluoxetine (25 mg/kg/day) during mid-gestation (prenatal day 15) through postpartum (postnatal day 12) decreased anxiety-like behavior in adult male (Kiryanova and Dyck, 2014) and female mice (McAllister et al, 2012). Together, this highlights the importance of dose and timing of fluoxetine as crucial methodological factors when evaluating effects of maternal fluoxetine on offspring outcome (reviewed in Kiryanova et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…For example, pre-gestational stress can affect the developing 5HT system as well as HPA axis reactivity in rat offspring (Gemmel et al, 2017;Gemmel et al, 2018c;Huang et al, 2013;Huang et al, 2010;Huang et al, 2012). Expanding on previous work we expected that pSSRIs would increase social interactions in female offspring, while pre-gestational maternal stress would decrease social behaviors in male offspring, with the exception of social play (pouncing/nape attacks) which has been linked to serotonin levels (Kepser and Homberg, 2015;Kiryanova and Dyck, 2014). We predicted that pSSRIinduced effects on social interactions would be related to alterations in the HPA system as well as the…”
Section: Introductionmentioning
confidence: 93%